The black concentration camps of the Anglo-Boer War 1899-1902 : shifting the paradigm from sole martyrdom to mutual suffering (Historia, 2021)
F.A. Van Jaarsveld opened a lecture to the Afrikaans Cultural Council of Pretoria, almost four decades ago, with these words : At the present time one is frequently confronted with assertion that the Afrikaner people has been assigned a place in the southern corner of Africa for a 'purpose' and to fulfil 'a mission'. Concomitant with this idea of the Afrikaner and his calling and mission is the idea that the Afrikaners are just like Old Israel, i.e. chosen people of God. Van Jaarsveld saw the sacred history of the Afrikaners as a series of suffering events experienced by the Afrikaner people, and out of which arose a belief in themselves as the Chosen People of God, called to a mission. It was because of their suffering that they knew that they were chosen people.
Keywords: chosen people; Afrikaners; Afrikaans Cultural Council of Pretoria; F.A. Van Jaarsveld; black concentration camps; Anglo-Boer War 1899-1902; mutual suffering